Ritual Context of Religious Conversion in a Short Story Ljuta neman (Angry Monster) Written by Grigorije Božović - Jevtić, Jelena (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
In the darkness of Turkish feudalism, the Serbian people fought to preserve their identity through the ritual and customary practice and tradition. The aim of this paper, which analyzes the short story entitled Ljuta neman (Eng. Angry Monster) by Grigorije Božović, is to determine the function of rituals as a communication channel and regulations in a social community with disturbed harmony. Religious conversion as a kind of violation of customs and destruction of harmony as a consequence brings the psychological drama of the search for identity that the those who were converted experienced, always torn between what they were and what they were not.
Keywords: ritual; religious conversion; destruction of harmony; sacred and profane; loss of identity; punishment